Rozwiąż równania:
-3x = 2x- 10
2x - 2 = 7 - x
10 = 4- 2x
-(2x - 1) = 4
2(x + 1) = x
2t - (3t + 1) = 6
-(4 + x) = 2(3 -x)
3(y +6) - y = 2(y +9)
(x - 7) - 2(3x + 5) = 5
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
-3x = 2x- 10
-3x-2x=-10
-5x=-10:(-5)
x=2
2x - 2 = 7 - x
2x+x=7+2
3x=9:3
x=3
10 = 4- 2x
2x=4-10
2x=6:2
x=3
-(2x - 1) = 4
2x+1=4
2x=4-1
2x=3:2
x=3/2=1i1/2
2(x + 1) = x
2x+2=x
2x-x=-2
x=-2
2t - (3t + 1) = 6
2t-3t-1=6
2t-3t=6+1
t=7
-(4 + x) = 2(3 -x)
-4-x=6-2x
-x+2x=6+4
x=10
3(y +6) - y = 2(y +9)
3y+18-y=2y+18
3y-y-2y=18-18
0=0
(x - 7) - 2(3x + 5) = 5
x-2-6x-10=5
x-6x=5+10+2
5x=17:5
x=17/5=3i2/5
Mam nadzieję że pomogłam:)
-3x=2x-10
-3x-2x= -10
-5x= -10 /:-5
x=2
2x-2=7-x
2x+x=7+2
3x=9 /:3
x=3
10=4-2x
2x=4-10
2x= -6 /:2
x= -3
-[2x-1]=4
-2x+1=4
-2x=4-1
-2x=3 /:-2
x= -3/2
x= -1 1/2
2[x+1]=x
2x+2=x
2x-x= -2
x= -2
2t-[3t+1]=6
2t-3t-1=6
2t-3t=6+1
-1t=7 /*-1
t= -7
-[4+x]=2[3-x]
-4-x=6-2x
-x+2x=6+4
x=10
3[y+6]-y=2[y+9]
3y+18-y=2y+18
3y-y-2y=18-18
0=0
[x-7]-2[3x+5]=5
x-7-6x-10=5
x-6x=5+7+10
-5x=23 /:-5
x= -23/5
x= -4 3/5